Penyebab Wajib Pajak Tidak Patuh - Rahayu, Dewi Pudji (Universitas Muhammadiyah Prof. DR HAMKA., 2017)
This study aims to determine the causes of non-compliance with taxpayers. Using qualitative methods, this study was conducted by interviewing fifteen taxpayers who have not complied with tax reporting to article 21 until 31 March 2015. Non-compliance includes both not reporting and not accurately calculating their taxes. Fifteen samples. The results showed that knowledge of tax laws and transparency of tax expenditures significantly affect taxpayer voluntary compliance.